Living donor kidney transplantation in patients with donor-specific HLA antibodies enabled by anti-CD20 therapy and peritransplant apheresis - Klein, Katrin; Süsal, Caner; Schäfer, Sebastian Markus; Becker, Luis Eduardo; Beimler, Jörg; Schwenger, Vedat; Zeier, Martin; Schemmer, Peter; Macher-Göppinger, Stephan; Scherer, Sabine; Opelz, Gerhard; Morath, Christian (Atherosclerosis. Supplements, 2013)
Objective - Due to increasing waiting times for deceased donor kidneys, living donor kidney transplantation is increasingly performed in the presence of donor-specific antibodies (DSA). - Methods - Twenty-three patients with Luminex-detected DSA were successfully desensitized by anti-CD20 therapy and immunoadsorption (N = 19) or plasmapheresis (N = 4) and received a kidney transplant from a living donor. Twelve of the 23 patients (52%) had a positive CDC and/or ELISA crossmatch result before desensitization. Six patients were negative in CDC as well as ELISA screening but positive in Luminex for DSA. - Results - The 23 patients received a median of 8 apheresis treatments before and 5 treatments after transplantation. Induction therapy was performed with either thymoglobulin (N = 11) or basiliximab (N = 12). The 2-year graft survival rate was 100%. At last follow up, a median of 12 months after transplantation, median serum creatinine was 1.42 mg/dL, median MDRD-GFR 59.5 mL/min/1.73 m2, and median urinary protein-to-creatinine ratio 0.12. Ten out of fourteen patients (71%) who had completed the first year after transplantation by the time of analysis had no DSA by day 360. Acute T-cell mediated rejection was diagnosed in one patient (4%), and antibody-mediated changes were found in 5 patients (22%). Four out of these 5 patients showed evidence of persistent (N = 2) or reemerging plus/minus de novo DSA (N = 2) on day 360, and the 2 patients with persistent DSA lost their allograft subsequently on days 750 and 810, respectively. Infectious complications were infrequent. - Conclusions - Our previously described treatment algorithm for desensitization of living donor kidney transplant recipients with DSA results in good graft outcomes with a low rate of side effects.
Gesehen am 08.06.2022